The Caste System and the Perspective of Indian Courts: Navigating Tradition and Equality - Prem Kumar Gautam, (AG Volumes, 2026)
The caste system, deeply entrenched in the fabric of Indian society, has played a pivotal role in shaping social structure, identities, and interactions for centuries. With roots stretching back to ancient times, the caste system remains a complex and controversial phenomenon that continues to impact millions of lives in contemporary India. The origins of the caste system can be traced to ancient scriptures like the Rigveda, where references to Varnas (social classes) are found. The caste system gradually evolved into a rigid hierarchical structure, with four main Varnas: Brahmins (priests and scholars), Kshatriyas (warriors and rulers), Vaishyas (merchants and artisans), and Shudras (laborers and service providers). Outside this system were those considered “downtrodden” or “Untouchables”, who were often subjected to extreme social exclusion and discrimination. The caste system's hierarchical structure has created a deeply ingrained social stratification that influences every aspect of life. While India has undergone significant social, economic, and political transformations, the caste system's influence endures. Untouchables and other marginalized communities continue to experience discrimination, violence, and limited access to education and employment opportunities. The reservation system, introduced to counter these disparities, allocates quotas in educational institutions and government jobs for historically disadvantaged groups. However, debates persist about the effectiveness of reservations and their potential to foster resentment among other segments of society. The perspective of Indian courts on this deeply ingrained system reflects the struggle to balance the preservation of cultural heritage with the imperative of upholding equality and human rights. The Indian courts on the caste system reflect the nation's evolving journey towards a more just and equitable society. The court’s efforts to balance tradition with the imperative of equality demonstrate a commitment to upholding constitutional values while respecting cultural diversity. As India navigates the delicate terrain of addressing historical inequities, it is the evolving perspective of its’ courts that continues to shape the narrative of change, challenging deeply rooted norms and striving for a future that dismantles the caste system’s hierarchies and embraces the principles of dignity, equality, and social justice. This chapter delves into the historical origins, hierarchical structure, and persistent challenges the caste system poses while exploring ongoing efforts of the judiciary to address these challenges. This will also delve into the evolving stance of Indian courts towards the caste system, examining landmark cases and their implications for social justice